Morphology-Controlled Synthesis Of SrTiO3 Nanocube By Capping Agent-Assisted Solvothermal Method - Yulia Eka Putri; Alvionita Alvionita; Rini Rahma Yanti; Diana Vanda Wellia (Universitas Jenderal Soedirman, 2016)
The synthesis of SrTiO3 nanocubes have been carried out by solvothermal process using cetyl trimethyl ammonium bromide (CTAB) as capping agent to control the particles morphology. The condition of the synthesis was obtained at 160 ºC for 24 hours with molar ratio of SrTiO3 and capping agent was 1 : 1. The X-ray diffraction (XRD) pattern shows that SrTiO3 adopts a perovskite structure with a higher intensity of 110 at 2q:32.33º and the crystallite size calculated from FWHM was found to be 41 nm. Fourier transform infrared (FTIR) spectrum shows a shift in particular absorption band attributed the interaction between SrTiO3 particles surface and the head group of CTAB molecules. Transmission electron microscopy (TEM) image shows the cubic-like particles of SrTiO3, this indicatesthat CTAB successfully functions as capping agent on the synthesis of SrTiO3.